2018
DOI: 10.1016/j.jpeds.2017.09.080
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Gastric Acid Inhibitors Increases the Risk of Infection in Preterm Very Low Birth Weight Infants but Concomitant Administration of Lactoferrin Counteracts This Effect

Abstract: isrctn.org: ISRCTN53107700.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…It displays antimicrobial and anti-infectious activity, with many clinical trials reporting its preventative role in neonatal sepsis, diarrhea, and necrotizing enterocolitis in preterm infants. High levels of lactoferrin are reported in colostrum 7 ng/L, with a gradual decline to 2-4g/L in mature milk [133][134][135][136][137]. Human milk contains an array of specialised growth factors such as epidermal growth factor, which aids healing of intestinal mucosa, insulin-like growth factors (IGF) 1 and 2 which increase tissue growth, and neuronal growth factors which help peristalsis; these are just some of the growth factors present in human milk that enhance infant development [138][139][140][141].…”
Section: Other Bioactive Compoundsmentioning
confidence: 99%
“…It displays antimicrobial and anti-infectious activity, with many clinical trials reporting its preventative role in neonatal sepsis, diarrhea, and necrotizing enterocolitis in preterm infants. High levels of lactoferrin are reported in colostrum 7 ng/L, with a gradual decline to 2-4g/L in mature milk [133][134][135][136][137]. Human milk contains an array of specialised growth factors such as epidermal growth factor, which aids healing of intestinal mucosa, insulin-like growth factors (IGF) 1 and 2 which increase tissue growth, and neuronal growth factors which help peristalsis; these are just some of the growth factors present in human milk that enhance infant development [138][139][140][141].…”
Section: Other Bioactive Compoundsmentioning
confidence: 99%
“…Lf plays a key role in specialized systems to bind iron, affecting cellular proliferation and differentiation, dependent on the degree of iron saturation [9,10]. Clinical trials have demonstrated roles for Lf in the prevention of diarrhea [11,12], neonatal sepsis, and necrotizing enterocolitis in preterm infants [13,14,15]. Lf may significantly impact development as well as the well-being of infants and later outcomes, which are directly related to breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…Lactoferrin (Lf) is an iron-binding glycoprotein involved in a wide range of biological functions including anti-infectious, antimicrobial, anti-inflammatory, immunomodulatory, and prebiotic activities, as well as promotion of cellular proliferation and differentiation [ 1 , 2 ]. Importantly, clinical trials have demonstrated roles for Lf in prevention of diarrhea [ 3 , 4 ], neonatal sepsis, and necrotizing enterocolitis in preterm infants [ 5 , 6 , 7 ]. It is secreted by exocrine glands and secondary neutrophils and mainly present in external secretions such as milk, saliva, tears, bile, and pancreatic fluids [ 8 ].…”
Section: Introductionmentioning
confidence: 99%